Online monitoring of structural materials integrity in process industry for I4.0: A focus on material loss through erosion and corrosion sensing. (May 2021) - Meribout, Mahmoud; Mekid, Samir; Kharoua, Nabil; Khezzar, Lyes
Abstract: This paper presents a critical review of the main sensing techniques considered for online monitoring of the integrity of alloys steel-made equipment used in process industry. This includes pipelines, tanks, electrical transformers and other metallic structures used in construction of buildings and bridges. Radio frequency (RF), Magnetic flux leak (MFL), ultrasonic-acoustic, fiber brag grating (FBG), thin layer strips, and photoacoustic sensors remain the main sensing techniques used or suggested for this purpose. However, despite lot of research works to improve their sensitivity and accuracy, further efforts are required to have them readily operational in the field especially for covering large volumes. This can be facilitated by the significant development carried out in various areas related to information technology (IT) and instrumentation, such as optical fiber sensors and self-powered wireless sensors under I4.0 paradigm. While optical fiber sensors, particularly FBG sensors, have the advantage to be scalable to cover wide areas with a few number of wires, they encounter the challenge of being not highly sensitive, especially for detecting degradations e.g. corrosion and erosion occurring at the opposite side of the steel structure. In addition, for such types of degradations, the fiber needs to be permanently and tightly connected to the structure, which is difficult to sustain. In addition, their proportional cost to the target sensitivity and resolution remains expensive. Wireless sensors equipped with ultrasonic sensors remain another tangible potential alternative for detecting internal corrosion and erosion of the structures if some pending issues relevant to power supply, using for instance energy harvesting, are sorted out. Overall, the existing technologies still suffer from a lack of sensitivity, accuracy, universality and/or cost effectiveness which justifies that more development efforts need to be done.